Математичне та комп’ютерне моделювання автономної контрроторної вітроустановки з трансформатором із обертовою половиною - Щур, Ігор Зенонович; Ковальчук, Андрій Іванович; Дзьоба, Тарас Ярославович (НТУ "ХПІ", 2013)
A comparative analysis of the simulation results on the computer model and the results of physical experiments on the model, which confirmed the high adequacy of computer model, is investigated. In order to optimize the energy-cost designs, for different power of wind turbines a simplified mathematical model of the wind turbines for the first harmonics in steady-state mode is developed. Comparison of the relative values of the intermediate coordinates derived from mathematical models and computer simulations shows acceptable for the planned research divergence that does not exceed 14%.
Mathematical modeling and computer simulation of stand-alone contra-rotor wind turbine with a transformer with rotating half
Keywords: вітроелектроустановки; вертикальна вісь обертання; стартова швидкість вітру; контрротор; енергетично-вартісна оптимізація